Le risque instrumentalisé ? Expertise scientifique et légitimité citoyenne : le cas de l’assainissement de la décharge industrielle de Bonfol en Suisse - Cecchini Amaranta (VertigO)
This article explores how social and scientific rationalities came into play in the context of the decontamination of the Bonfol (Switzerland) industrial dumping ground, and what consequences resulted from it. The exposure of the sanitary and environmental risks is at once based on the criticism of the technical/scientific statements and of the scientific survey, which however tends to lose its legitimacy as it becomes part of a political debate. Still, scientific data remains a crucial justifying tool in the conflict. Non-specialists must then adapt themselves and rely on a scientific discourse, while still being able to raise other arguments that redefine the environmental problem.